Left ventricle inflow and outflow tract angle in normal fetuses - Yang, Yang; Xu, Ran; Tan, Heyi; Zhou, Dan; Zhou, Jiawei; Zeng, Shi (Frontiers in Cardiovascular Medicine, 2023)
Objective Impaired elasticity of aorta has been observed in fetuses with congenital cardiac disease, while the orientation of left ventricle outflow tract has been found to influence the blood flow in the ascending aorta. Therefore, the objective of this study is to examine the left ventricle inflow and outflow tract angle (LIOA) in healthy fetuses. Method A total of 668 fetuses were enrolled in this prospective study. The LIOA were measured with two-line method at left ventricle inflow and outflow tract view. Pearson's correlation coefficient was utilized to assess the associations between LIOA and estimated fetal weight (EFW) and cardiac dimensions, including cardiac axis and diameters of aortic valve (AV), pulmonary artery valve (PAV), mitral valve (MV) and tricuspid valve (TV). Results The LIOA was determined to be 44 ± 7.5° (mean ± SD). No significant difference was observed in the LIOA across different gestational ages (GAs). A mild positive correlation was observed between LIOA and cardiac axis. However, no significant associations were found between LIOA and parameters such as EFW, as well as diameters of AV, PAV, MV and TV. Conclusion The LIOA remained constant during the mid-third trimester and was mildly positively correlated with cardiac axis in normal fetuses.